Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen KAI Di Solo Raya - Dinnova Ryo Kristanto; Rayhan Gunaningrat (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
PT Kereta Api Indonesia (KAI) is a company that monopolizes unrivaled rail transport services, but on Java Island it is vulnerable to competitors in other transport services sectors in the world. The purpose of this study was to find out whether the influence of price and quality of service on the satisfaction of railway consumers in the city of Solo Raya. Sampling technique using quota sampling and random sampling techniques with respondent criteria is consumer satisfaction in using railway services, which is 51 respondents. Data collection is done using questionnaires distributed online or electronically using Google Form support. The results of the study showed that the influence of price and quality of service has a significant influence on consumer satisfaction.